1984
DOI: 10.1161/01.hyp.6.5_pt_2.ii40
|View full text |Cite
|
Sign up to set email alerts
|

Effects of methyldopa metabolites on amine transmitters and adrenergic receptors in rat brain.

Abstract: Studies of catecholamine concentrations in defined nuclei from the anterior hypothalamic-preoptic regions and the medulla oblongata, known to contribute to cardiovascular control, were measured following acute or chronic methyldopa administration. These studies indicated that methyldopa was enzymatic-ally converted to methyldopamine and methylnorepinephrine, and in some areas to methylepinephrine which replaced endogenous epinephrine. The predominant metabolite was methylnorepinephrine, which accumulated in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The NTS is the site of the hypotensive action of ␣-methyl-norepinephrine (␣-MNA), the active metabolite of ␣-methyl-dopa, which is a catecholamine, full agonist at ␣ 2 -adrenoceptors. 10,11 The RVLM/NRL is the major site of the hypotensive effect of imidazoline drugs such as clonidine and rilmenidine, which requires specific imidazoline receptors, insensitive to catecholamines. [12][13][14][15][16][17] Ma et al 18 showed that N G -nitro-L-arginine methyl ester, an NOS inhibitor applied directly into the NTS, inhibited the electrical activity of the cardiovascular neurons.…”
mentioning
confidence: 99%
“…The NTS is the site of the hypotensive action of ␣-methyl-norepinephrine (␣-MNA), the active metabolite of ␣-methyl-dopa, which is a catecholamine, full agonist at ␣ 2 -adrenoceptors. 10,11 The RVLM/NRL is the major site of the hypotensive effect of imidazoline drugs such as clonidine and rilmenidine, which requires specific imidazoline receptors, insensitive to catecholamines. [12][13][14][15][16][17] Ma et al 18 showed that N G -nitro-L-arginine methyl ester, an NOS inhibitor applied directly into the NTS, inhibited the electrical activity of the cardiovascular neurons.…”
mentioning
confidence: 99%
“…The brain stem structures of the baroreflex arch include the nucleus tractus solitarii and the nucleus reticularis lateralis of the rostral ventrolateral medulla (NRL/RVLM). The nucleus tractus solitarii is a major source of afferent inputs to the NRL/RVLM [4,5], and the site of action of a 2 -ARs ligands such as a-methyl-noradrenaline, a catecholamine selective for a 2 -ARs [6,7]. The NRL/RVLM is an important integrative center of sympathetic control that plays a crucial role in the tonic and phasic regulation of arterial BP [8].…”
Section: Introductionmentioning
confidence: 99%